Coercive care and human rights; a complex juxtaposition – part 2. (October 2019) - Little, John D
Objective: To examine capacity assessment, coercive care and principles by which a seemingly reasonable request for the discontinuation of treatment may be considered. Conclusions: A clinical and socio-legal case may be made for 'coercive care'.